2020
DOI: 10.1038/s41467-019-13976-8
|View full text |Cite
|
Sign up to set email alerts
|

Strong inverse kinetic isotope effect observed in ammonia charge exchange reactions

Abstract: Isotopic substitution has long been used to understand the detailed mechanisms of chemical reactions; normally the substitution of hydrogen by deuterium leads to a slower reaction. Here, we report our findings on the charge transfer collisions of cold Xe þ ions and two isotopologues of ammonia, NH 3 and ND 3. Deuterated ammonia is found to react more than three times faster than hydrogenated ammonia. Classical capture models are unable to account for this pronounced inverse kinetic isotope effect. Moreover, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 51 publications
0
38
0
1
Order By: Relevance
“…These findings build upon an earlier study, where we identified a significant KIE in the charge transfer of Xe + with ammonia isotopologues. 1 Secondary inverse KIEs are relatively uncommon, having only been identified in a handful of previous studies. In systems where secondary inverse KIEs have been seen, they are typically modest effects (with k H /k D = 0.8 − 0.9).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings build upon an earlier study, where we identified a significant KIE in the charge transfer of Xe + with ammonia isotopologues. 1 Secondary inverse KIEs are relatively uncommon, having only been identified in a handful of previous studies. In systems where secondary inverse KIEs have been seen, they are typically modest effects (with k H /k D = 0.8 − 0.9).…”
Section: Discussionmentioning
confidence: 99%
“…For the recording of rate coefficients, we follow the protocol described in a previous study involving Xe + charge transfer reactions. 1 Kr is introduced through a high-precision leak valve, with Kr + ions formed using a (2 + 1) REMPI scheme at 212.6 nm (utilising the tripled output of a Nd:YAG-pumped dye laser). A subset of Kr + ions are produced in the higher energy 2 P 1/2 spin state.…”
Section: A Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations